ChemInform Abstract: Unexpected O‐Alkylation and Ester Migration in Phenolic 2, 3‐Diaryl‐2, 3‐dihydrobenzo[b]furans. Issue 31 (11th July 2013) - Tran, Henry; Dickson, Benjamin D.; Barker, David
Abstract Attempted O‐alkylation of benzodihydrofuran derivative (I) proceeds through an unexpected hydrolysis of the nitrobenzoate esters accompanied by transfer of a ‐Pnb group to the aromatic 5‐OH and double alkylation of the newly generated 3, 5‐dihydroxyphenyl moiety.